Congenital Bochdalek’s Diaphragmatic Hernia - Ahmadu, Baba Usman; Yola, Chinda John; Abew, Kaleb Abalis (Journal of Nepal Paediatric Society, 2013)
Diagnosis of a rare Bochdalek’s congenital diaphragmatic hernia may be challenging. Our patient presented with respiratory and gastrointestinal findings. Chest radiograph revealed the stomach in the left thorax. Diagnosis of recurrent bacterial pneumonia was incorrectly made because of repeated symptoms. Chest radiograph can provide sufficient information for rapid diagnosis. DOI: http://dx.doi.org/10.3126/jnps.v32i3.6968 J. Nepal Paediatr. SocVol.32(3) 2012 254-256